The roles of electronic dictionaries in language learning from 2010-2024: a bibliometric review - Samsuri, Maimanah; Muslim, Mazni; Abdul Manap, Nurma; Mazlan, Siti Aisyah (GADING Journal for the Social Sciences, 2024)
Mastery of vocabulary is crucial in the teaching and learning process. Students need to memorise and identify words to complete their tasks. As a result, electronic dictionaries are essential. The current study identified research trends regarding the role of electronic dictionaries in language learning. By searching journals related to electronic dictionaries indexed in the Elsevier Scopus database between the 2010 and 2024 period, we collected 274 research articles in total. The results obtained by bibliometric analysis showed that the role of electronic dictionaries is still volatile in published journals. We concluded that the researchers are language experts, and the United States of America has the most linked countries in co-authorship. Also, the research gap mainly focuses on three critical keywords: electronic dictionaries, online dictionaries and lexicography. For further research, it is recommended that a more in-depth study be conducted on methods for the effectiveness of using electronic dictionaries in language learning.